Complex intertwined association between breastfeeding practices and household food insecurity: Systematic review and meta‐analysis - Gabriela Buccini; Cali Larrison; Smriti Neupane; Maria Palapa; Raquel Machado Schincaglia; Sara Brown; Muriel B. Gubert (Wiley, 2024)
Abstract Breastfeeding offers ideal food and nutrition for infants; however, structural barriers may amplify breastfeeding inequities. We aimed to identify whether household food insecurity (HFI) is associated with exclusive and continued breastfeeding (EBF and CBF) as recommended by the World Health Organization/United Nations Children's Fund (UNICEF) Following the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis, literature searches using 'breastfeeding', 'food insecurity' and 'infant' terms were conducted in PubMed/MEDLINE, Embase, CINAHL, Global Health and LILACS from inception through November 2023, without language restrictions, yielding 1382 publications (PROSPERO:CRD42022329836). Predetermined eligibility criteria yielded the 12 included studies (nine cross‐sectional and three cohorts). The risk of bias was assessed through the Effective Public Health Practice Project. Meta‐analysis was performed for studies assessing EBF (n = 10), and metaregression was used to explore heterogeneity across studies. Prevalence of EBF ranged from 1.6% to 85.3%, with a lower prevalence among HFI. The pooled effect of the association between HFI and EBF presented an odds ratio (OR) of 0.61 (95% CI = 0.49-0.76) with consistent results across marginal (OR = 0.72, 95% CI = 0.55-0.94), moderate (OR = 0.59, 95% CI = 0.41-0.84) and severe HFI (OR = 0.49, 95% CI = 0.32-0.76). High heterogeneity was found only when HFI was dichotomized. The prevalence of CBF ranged from 35.4% to 78.0%, with inconsistent prevalence among HFI; a meta‐analysis was not performed due to the low number of studies (n = 3). We concluded that HFI levels are associated with lower odds of EBF. Integrating service and policy‐level strategies, such as screening, referrals, skilled breastfeeding counseling and access to comprehensive nutrition and social programs, could reduce structural inequities and promote adherence to the World Health Organization/UNICEF breastfeeding recommendations among food‐insecure families.